Influence of friction condition on failure location of AA5754 aluminium sheet in Nakajima test - Jan Slota; Marek Šiser (Advances in Mechanical and Materials Engineering, 2018)
This paper presents the results of numerical and experimental investigations on the influence of friction on failure location in Nakajima formability tests. Finite element (FE) simulations were performed using commercial explicit dynamic FE code. The numerical results obtained from the FE simulation were compared with experimental data from Nakajima tests. A 3D digital image correlation system ARAMIS was used in experiments. The location of failure on the sample was detected depending on friction conditions. The studies confirmed that the crack location near the centre of the specimen as required by the ISO standard could be obtained for low values of the friction coefficient. The numerical simulation combined with the inverse analysis was used to estimate a real value of the friction coefficient in the Nakajima formability test.